Powerline communication in electric vehicles - Ezio Bassi (2009)
In full electric (EV) or hybrid electric (HEV) vehicles the onboard communication is a crucial issue, that can take advantage from a reliable and robust interaction among the embedded units (ECUs) providing among others the power and batteries management, services, accessories and supervision; an updated global view of the system under control (the car) can improve the quality of control, reliability, safety and comfort. Power Line Communication technology (PLC), that take advantage of the DC power line as a physical medium to exchange messages, according to standard protocols, is a candidate at substituting the actual wired solutions, by substantially reducing the cabling burden. The present paper aims at i) reviewing PLC technology for DC bus in the automotive sector; ii) defining the requirements of a reliable communication systems within a car environment, with special attention given to the data exchange needed by the more critical systems in EV and HEV, and namely the control of electrical actuators for traction; iii) describing a benchmark for testing the data transfer characteristics and performance, including details on proposed protocols and architectures and presenting experimental results on data channel characterization and transmission. Â(c) 2009 IEEE.